Bilateral Psoas Muscle Abscess Associated with Emphysematous Cystitis - Jae-Ki Choi; Jae-Cheol Kwon (Case Reports in Medicine)
Psoas muscle abscess associated with emphysematous urinary tract infection is very rare. There were very few reports about urinary tract infections such as renal abscess, perinephric abscess, and emphysematous pyelonephritis complicated with psoas muscle abscess; however, psoas muscle abscess associated with emphysematous cystitis has not yet been reported. Here, we report a case of bilateral posas muscle abscess following emphysematous cystitis in an 81-year-old nondiabetic man, who was treated successfully with prolonged antibiotic therapy and supportive care. Early recognition of psoas muscle abscess can prevent aggressive interventional procedure and warrant good prognosis.